2022
DOI: 10.1038/s41598-022-19335-w
|View full text |Cite
|
Sign up to set email alerts
|

SMAD3 contributes to ascending aortic dilatation independent of transforming growth factor-beta in bicuspid and unicuspid aortic valve disease

Abstract: We sought to determine whether there are differences in transforming growth factor-beta (TGFß) signaling in aneurysms associated with bicuspid (BAV) and unicuspid (UAV) aortic valves versus normal aortic valves. Ascending aortic aneurysms are frequently associated with BAV and UAV. The mechanisms are not yet clearly defined, but similarities to transforming growth factor-beta TGFß vasculopathies (i.e. Marfan, Loeys-Dietz syndromes) are reported. Non-dilated (ND) and aneurysmal (D) ascending aortic tissue was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…It is known that rs17684886 in ZNRF1 is associated with diabetic retinopathy [ 81 ], and its expression is induced in peripheral nerves after injury [ 82 ], so its overexpression causes neurite-like elongation. It has been found that expression of the SMAD2 protein is progressively increased in reactive lesions and oral submucous fibrosis (OSMF) [ 83 ], and SMAD3 contributes to ascending aortic dilatation independently of transforming growth factor-beta in bicuspid and unicuspid aortic valve disease [ 84 ], which is consistent with our data.…”
Section: Discussionsupporting
confidence: 92%
“…It is known that rs17684886 in ZNRF1 is associated with diabetic retinopathy [ 81 ], and its expression is induced in peripheral nerves after injury [ 82 ], so its overexpression causes neurite-like elongation. It has been found that expression of the SMAD2 protein is progressively increased in reactive lesions and oral submucous fibrosis (OSMF) [ 83 ], and SMAD3 contributes to ascending aortic dilatation independently of transforming growth factor-beta in bicuspid and unicuspid aortic valve disease [ 84 ], which is consistent with our data.…”
Section: Discussionsupporting
confidence: 92%
“…Studies focusing on the TGF-β signaling pathway in BAV patients on tissue level found a decreased expression of TGF-β and the downstream signalers phosphorylated SMAD2 (pSMAD2) and SMAD3 (pSMAD3) in the non-and dilated aorta of BAV patients [8][9][10] ( Table 1 ). Recently, Balint et al also found that in the dilated aorta of BAV patients the expression of TGFß1 is significantly lower as compared to the dilated TAV patients [11] . Interestingly, the authors described that in BAV patients the pSMAD2/pSMAD3 and TGFß1 expressions were not correlated [11] ( Table 1 previous study, we reported a non-homogenous expression pattern of TGF-ß in the aortic wall.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, Balint et al also found that in the dilated aorta of BAV patients the expression of TGFß1 is significantly lower as compared to the dilated TAV patients [11] . Interestingly, the authors described that in BAV patients the pSMAD2/pSMAD3 and TGFß1 expressions were not correlated [11] ( Table 1 previous study, we reported a non-homogenous expression pattern of TGF-ß in the aortic wall. We found that TGF-ß is mainly expressed in the outer media and that the inner and middle media are completely devoid of TGFß.…”
Section: Introductionmentioning
confidence: 95%
“…Medial accumulation of mucoid extracellular matrix components is significantly higher in non-dilated and dilated BAV patients as compared to the TAV (Fig. 4 D) [ 37 , 59 ].…”
Section: The Ascending Aortic Wall Development and Histology In The B...mentioning
confidence: 99%